Property regime preferences of newly married individuals - Villanueva, Nancy Grace Lozare
This paper is an exploratory study of how married individuals would prefer their property with respect to those they owned before and during their marriage. Fifty (50) married individuals were interviewed using a researcher-made interview guide consisting of 22 questions which pertain to various properties before and during marriage. Reasons for their answers were also asked to determine why they preferred certain properties to be considered as conjugal or separate. The study found that the most preferred property regime is conjugal partnership of gains, the second being absolute community of properties. It also showed that there is no general preference for complete separation of properties. The findings were: 1. The respondents preferred separation of properties before marriage because the properties acquired before marriage were intended for him/her self and his own parents and siblings. 2. The respondents preferred conjugal partnership of gains during marriage: a. because they did not want money or material possessions to be source of conflict between their spouses or among their families. b. to male respondents, so that the whole family will benefit from his properties, and easily in case he dies or leaves. c. to female respondents, because, anyway in most cases, their husbands' financial capacity is not sufficient to meet the needs of the whole family. 3. During marriage, the respondents: a. have indicated their desire to help their own parents and siblings although they put priority to their new families: own spouse and children. b. discussed with their spouses their property relations only casually. 4. Variations in property regime preferences were based on sex and monthly income. However, religious affiliation and educational attainment were not determining factors in property regime references. Future studies should 1. probe deeper into the reasons why certain properties, personal and real, are considered as common or separate; 2. determine variations in property regime preferences based on sex and monthly income; and, 3. obtain a bigger sampling population and stratify these respondents according to the following: age, occupation, stage in the family life cycle, and economic levels.